IN WHAT WAYS CAN UZBEK BANKS ACCEPT THE PRINCIPLES OF EQUATOR AND BECOME MEMBERS? - Utbasarov , Oybek Ixtiyor o‘g‘li; Saydaliyeva , Lazizaxon Ulug‘bek qizi (Educational Research in Universal Sciences, 2023)
This article talks about the ways in which the banks of Uzbekistan can adopt the Equator principles and become members, as well as important suggestions for adopting the Equator principles.